2010
DOI: 10.1103/physrevb.81.205111
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and anomalous band-edge absorption feature in multiferroicMnWO4: An optical spectroscopic study

Abstract: We investigated the electronic structure and lattice dynamics of multiferroic MnWO 4 by optical spectroscopy. With variation of polarization, temperature, and magnetic field, we obtained optical responses over a wide range of photon energies. The electronic structure of MnWO 4 near to the Fermi level was examined, with inter-band transitions identified in optical conductivity spectra above a band-gap of 2.5 eV. As for the lattice dynamics, we identified all the infrared transverse optical phonon modes availabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 38 publications
(47 reference statements)
6
23
0
Order By: Relevance
“…[40,41] and our data agree very well with each other. With the exception of the lowest A u mode, the values for ω 0,i agree within about 1-2 %.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…[40,41] and our data agree very well with each other. With the exception of the lowest A u mode, the values for ω 0,i agree within about 1-2 %.…”
supporting
confidence: 81%
“…With the exception of the lowest A u mode, the values for ω 0,i agree within about 1-2 %. In MnWO 4 , we and Choi et al 40 found the lowest mode at 168 cm −1 at room temperature, whereas it was reported at 180 and 182 cm Note that the values of the damping γ i and the oscillator strength ∆ε i are not reported for the single-crystal data in Refs. [40,41].…”
mentioning
confidence: 58%
See 3 more Smart Citations